Fulminating herpes simplex hepatitis - Raheel Ahmed; Kesley Green; Silvio Litovsky; Sameer Al Diffalha (University of São Paulo, 2022)
Herpes simplex virus (HSV) is a rare cause of acute hepatitis in patients with chronic immunosuppression, including Crohn's disease. HSV hepatitis has the propensity to cause acute liver failure and death. The presenting signs and symptoms can be nonspecific, thereby causing the diagnosis to go overlooked with inadequate management, leading to a high mortality rate. We report a case of a 31-year-old male on chronic prednisone treatment for Crohn's disease who unexpectedly died. Subsequently, an autopsy showed HSV hepatitis as the cause of death. Thus, although a rare complication, HSV hepatitis should always be kept in mind as a fatal complication in patients with acute hepatitis and chronic immunosuppression.